Use of E. coli OMVs as delivery system to elicit neutralizing antibodies against Chlamydia infectivity: the HtrA protein example - Ianni, Elvira <1981> (Alma Mater Studiorum - Università di Bologna, 2011)
The obligate intracellular pathogen Chlamydia trachomatis is a gram negative bacterium which infects epithelial cells of the reproductive tract. C. trachomatis is the leading cause of bacterial sexually transmitted disease worldwide and a vaccine against this pathogen is highly needed. Many evidences suggest that both antigen specific-Th1 cells and antibodies may be important to provide protection against Chlamydia infection. In a previous study we have identified eight new Chlamydia antigens inducing CD4-Th1 and/or antibody responses that, when combined properly, can protect mice from Chlamydia infection. However, all selected recombinant antigens, upon immunization in mice, elicited antibodies not able to neutralize Chlamydia infectivity in vitro. With the aim to improve the quality of the immune response by inducing effective neutralizing antibodies, we used a novel delivery system based on the unique capacity of E. coli Outer Membrane Vesicles (OMV) to present membrane proteins in their natural composition and conformation. We have expressed Chlamydia antigens, previously identified as vaccine candidates, in the OMV system. Among all OMV preparations, the one expressing HtrA Chlamydia antigen (OMV-HtrA), showed to be the best in terms of yield and quantity of expressed protein, was used to produce mice immune sera to be tested in neutralization assay in vitro. We observed that OMV-HtrA elicited specific antibodies able to neutralize efficiently Chlamydia infection in vitro, indicating that the presentation of the antigens in their natural conformation is crucial to induce an effective immune response. This is one of the first examples in which antibodies directed against a new Chlamydia antigen, other than MOMP (the only so far known antigen inducing neutralizing antibodies), are able to block the Chlamydia infectivity in vitro. Finally, by performing an epitope mapping study, we investigated the specificity of the antibody response induced by the recombinant HtrA and by OMV-HtrA. In particular, we identified some linear epitopes exclusively recognized by antibodies raised with the OMV-HtrA system, detecting in this manner the antigen regions likely responsible of the neutralizing effect.